2021
DOI: 10.1016/j.bioorg.2021.105145
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate peel extract polyphenols attenuate the SARS-CoV-2 S-glycoprotein binding ability to ACE2 Receptor: In silico and in vitro studies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…A more precise suggestion was made by Prussin II [21], who clearly indicated that the phi6 phage particles may be selected as a surrogate for coronaviruses. These assumptions were confirmed by Surucic et al [34] who indicated that pomegranate polyphenolic compounds have the potential to attenuate the ability of SARS-CoV-2 S-glycoprotein to bind to the ACE2 receptor and therefore to be excellent candidates for possible therapeutic application. It should be also mentioned that the authors suggest the possible synergistic effect of pomegranate polyphenols.…”
Section: Discussionmentioning
confidence: 72%
“…A more precise suggestion was made by Prussin II [21], who clearly indicated that the phi6 phage particles may be selected as a surrogate for coronaviruses. These assumptions were confirmed by Surucic et al [34] who indicated that pomegranate polyphenolic compounds have the potential to attenuate the ability of SARS-CoV-2 S-glycoprotein to bind to the ACE2 receptor and therefore to be excellent candidates for possible therapeutic application. It should be also mentioned that the authors suggest the possible synergistic effect of pomegranate polyphenols.…”
Section: Discussionmentioning
confidence: 72%
“…For example, PUG was identified as an allosteric inhibitor of SARS-CoV-2 3CLpro main protease ( Du et al, 2021 ; Khalifa et al, 2020 ; Tito et al, 2021 ), which functions to cleave the polyproteins to generate nonstructural proteins. Moreover, PUG was also shown to interfere with the interaction between the virus spike glycoprotein and the cellular receptor ACE2 ( Surucic et al, 2021 ; Tito et al, 2021 ), and thereby might have potential inhibitory effects on the virus entry into the host cells. Our results showed that PUG directly binds NSP13 with a KD value of 21.6 nM, inhibits the helicase activity of NSP13 (IC 50 ∼ 430 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Given this, it is interesting to note that urolithin metabolites can exert a mild anti-SARS-CoV-2 Mpro inhibition ( 113 ) at physiological relevant concentrations (2–50 μM), detectable in human colon tissues after consumption of hydrolyzable tannin-rich foods, as per clinical studies ( 114 ). Also, the pomegranate peel extract, punicalin, punicalagin, and UA have the potential to block the SARS-CoV-2 spike (S) glycoprotein receptor-binding domain (RBD)-ACE2 receptor on host cells contact, which is one of the first steps of virus infection ( 115 ). Additionally, it has been understood that SARS-Cov-2 can activate pro-inflammatory chemokines in the early stage, and this can lead to the development of either a protective immune response or an exacerbated inflammatory response ( 116 ).…”
Section: Coronavirus Disease (Covid-19)mentioning
confidence: 99%